2014
DOI: 10.1159/000368674
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of <b><i>UGT1A1</i></b> *<b><i>28/</i></b>*<b><i>6</i></b> Genotype-Directed Dosing of Irinotecan (CPT-11) in Korean Patients with Metastatic Colorectal Cancer Receiving FOLFIRI

Abstract: Purpose: A UGT1A1 genotype-directed dose escalation of irinotecan (CPT-11) was performed in patients with metastatic colorectal cancer receiving first-line FOLFIRI chemotherapy. Methods: Patients were genotyped for UGT1A1 and stratified according to the number of defective alleles (DA; *28 and *6). The irinotecan dose was escalated with a fixed dose of 5-fluorouracil and leucovorin in a standard 3 + 3 design. Results: In 43 enrolled patients, the maximum tolerated dose (MTD) was 300 mg/m2 for the 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…Importantly, investigations performed on Asian populations led to similar conclusions (some of these studies considered the *6 allele along with the*28) [63,64]. The majority of the irinotecan dose-escalation studies combining irinotecan with 5FU (with or without mAbs) have been performed in Caucasian patients.…”
Section: Genotype-directed Dose-escalation Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Importantly, investigations performed on Asian populations led to similar conclusions (some of these studies considered the *6 allele along with the*28) [63,64]. The majority of the irinotecan dose-escalation studies combining irinotecan with 5FU (with or without mAbs) have been performed in Caucasian patients.…”
Section: Genotype-directed Dose-escalation Studiesmentioning
confidence: 80%
“…Estimation of optimal doses according to genotype may be approximated from the eight clinical dose-escalation studies based on UGT1A1 genotype published so far [57][58][59][60][61][62][63][64]. Estimation of optimal doses according to genotype may be approximated from the eight clinical dose-escalation studies based on UGT1A1 genotype published so far [57][58][59][60][61][62][63][64].…”
Section: Genotype-directed Dose-escalation Studiesmentioning
confidence: 99%
“…5256 Three studies evaluating irinotecan doses in FOLFIRI showed that the maximal tolerated dose (MTD) in patients with *1/*1, *1/*28, and *1/*6 alleles was higher than the standard doses of the FOLFIRI regimen 5254. The MTD in the *1/*1 patients was also higher than that of patients with *1/*28 and *1/*6 alleles, and the MTD in patients with *28/*28, *6/*6, and *28/*6 alleles was lower than the current standard doses of the FOLFIRI regimen 53,54. In the Asian population, incorporation of UGT1A1*6 in addition to UGT1A1*28 would be needed for the safety of irinotecan-based chemotherapy.…”
Section: Genotype-based Dose Modification Studiesmentioning
confidence: 99%
“…Patients with uridine diphosphate glucuronosyltransferase ( UGT ) 1A1 *6 or *28 homozygous genotypes or with UGT1A1 *6 and *28 compound heterozygous genotypes received a lower irinotecan dose of 150 mg/m 2 . Treatment was continued in both arms until any one of the following occurred: disease progression, unacceptable toxicity, deterioration of ECOG performance status to >2, or withdrawal of patient consent.…”
Section: Methodsmentioning
confidence: 99%